Conservation of historic timber roof structures of Italian architectural heritage: diagnosis, assessment, and intervention. Issue 4 (19th May 2018) - Bertolini Cestari, Clara; Marzi, Tanja
ABSTRACT: In the context of our architectural heritage, timber structures represent an important sector in terms of historical relevance, architectural technology, and construction materials. In the past, these structures did not receive much attention in terms of conservation: they were frequently subject to inappropriate interventions or demolitions. Roof structures constitute an integral part of the architectural complex in which they are located and should be treated with the same attention and respect due to their historical significance. The conservation process of these structures has found a proper role in the preservation project partly as a result of technological innovations and regulations of the sector of wooden artefacts belonging to cultural heritage. This article presents multi-disciplinary research projects for the conservation and rehabilitation of historic timber roof structures carried out over a period of 30 years. The study involved ten roofs mainly belonging to the architectural heritage of northern Italy, of which five of them are included on the UNESCO World Heritage List.